2.3. LAGRANGIAN MECHANICS IN CONFIGURATION SPACE 33
to describe the dynamical evolution of the Compound Atwood Machine. This set of equa-
tions can, in fact, b e solved explicitly as
¨x = g
m
1
m
+
− ( m
2
+
− m
2
−
)
m
1
m
+
+(m
2
+
− m
2
−
)
!
and ¨y = g
2 m
1
m
−
m
1
m
+
+(m
2
+
− m
2
−
)
!
,
where m
±
= m
2
± m
3
. Note also that it can be shown that the position z of the center of
mass of the mechanical system (as measured from the top of the first pulley) satisfies the
relation
Mg(z − z
0
)=
m
1
2
˙x
2
+
m
2
2
(˙y − ˙x)
2
+
m
3
2
(˙x +˙y)
2
, (2.16)
where M =(m
1
+ m
2
+ m
3
) denotes the total mass of the system and we have assumed
that the system starts from rest (with its center of mass located at z
0
). This important
relation tells us that, as the masses start to move, the center of mass must fall.
At this point, we introduce a convenient technique (henceforth known as Freezing De-
grees of Freedom) for checking on the physical accuracy of any set of coupled Euler-Lagrange
equations. Hence, for the Euler-Lagrange equation (2.14), we may freeze the degree of free-
dom associated with the y-coordinate (i.e., we set ˙y =0=¨y or m
−
= 0) to obtain
¨x = g
m
1
− m
+
m
1
+ m
+
!
,
in agreement with the analysis of a simple Atwood machine composed of a mass m
1
on
one side and a mass m
+
= m
2
+ m
3
on the other side. Likewise, for the Euler-Lagrange
equation (2.15), we may freeze the degree of freedom associated with the x-coordinate (i.e.,
we set ˙x =0=¨x or m
1
m
+
= m
2
+
− m
2
−
) to obtain ¨y = g (m
−
/m
+
), again in agreement
with the analysis of a simple Atwood machine.
2.3.5 Example V: Pendulum with Oscillating Fulcrum
As a fifth and final example, we consider the case of a pendulum of mass m and length
` attached to a massless block which is attached to a fixed wall by a massless spring of
constant k; of course, we assume that the massless block moves without friction on a set of
rails. Here, we use the two generalized coordinates x and θ shown in Figure 2.7 and write
the Cartesian co ordinates (y,z) of the pendulum mass as y = x + ` sin θ and z = −` cos θ,
with its associated velocity components v
y
=˙x + `
˙
θ cos θ and v
z
= `
˙
θ sin θ. The kinetic
energy of the pendulum is thus
K =
m
2
v
2
y
+ v
2
z
=
m
2
˙x
2
+ `
2
˙
θ
2
+2` cos θ ˙x
˙
θ
.
The potential energy U = U
k
+ U
g
has two terms: one term U
k
=
1
2
kx
2
asso ciated with
displacement of the spring away from its equilibrium position and one term U
g
= mgz
asso ciated with gravity. Hence, the Lagrangian for this system is
L(x, θ, ˙x,
˙
θ)=
m
2
˙x
2
+ `
2
˙
θ
2
+2` cos θ ˙x
˙
θ
−
k
2
x
2
+ mg` cos θ.